2014
DOI: 10.1177/0267659114550234
|View full text |Cite
|
Sign up to set email alerts
|

Tissue perfusion in neonates undergoing open-heart surgery using autologous umbilical cord blood or donor blood components

Abstract: Despite the fact that the oxyhemoglobin dissociation curve is shifted leftward in patients who receive autologous umbilical cord blood, tissue oxygen delivery appears to be preserved in neonates who undergo open-heart surgery using autologous umbilical cord blood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…Several authors suggested the possibility of using cord blood as an alternative to adult blood transfusion . We reported four case reports and thirteen case series .…”
Section: Review Of Studies On Umbilical Cord Blood As a Source For Trmentioning
confidence: 94%
See 4 more Smart Citations
“…Several authors suggested the possibility of using cord blood as an alternative to adult blood transfusion . We reported four case reports and thirteen case series .…”
Section: Review Of Studies On Umbilical Cord Blood As a Source For Trmentioning
confidence: 94%
“…Several authors suggested the possibility of using cord blood as an alternative to adult blood transfusion . We reported four case reports and thirteen case series . Transfusions were performed because of neonatal anaemia in seven cases , surgical indications such as congenital malformations and cardiac surgeries in eight cases.…”
Section: Review Of Studies On Umbilical Cord Blood As a Source For Trmentioning
confidence: 99%
See 3 more Smart Citations